2022
DOI: 10.1097/scs.0000000000008577
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Cranial Aperture of the Optic Canal on Cone-Beam Computed Tomography Images and its Clinical Implications for the Transcranial Approaches

Abstract: Objective: This study aimed to investigate morphometric properties of the cranial aperture (CA) of the optic canal. Methods: Cone-beam computed tomography images of 400 individuals (200 males and 200 females) aged 37.32 ± 15.87 years were retrospectively examined to assess the morphometry and morphology of the CA. Results: The height and width of CA were found as 4.22 ± 0.74 mm and 7.27 ± 1.15 mm, respectively. The distances between the CA and the midsagittal line, the anterior and lateral boundaries of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
(168 reference statements)
0
2
0
Order By: Relevance
“…Knowing the morphometric values in surgical procedures to be performed in the region is very important for surgeons. In the surgical procedures planned for the relevant region, the region’s microanatomy, the anatomic features of the relevant region, and the reference values of the structures could be affected by the choice of the surgical intervention technique (eg, pterional, supraorbital, extracranial-transethmoidal, or transnasal approach) 3,4,22,24,25 . In a study performed with Indian adults aged 34.07 years by Gupta et al, 26 ONST was found as 4.83 mm (0.82), and 4.72 mm (0.74) on the left and right sides, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Knowing the morphometric values in surgical procedures to be performed in the region is very important for surgeons. In the surgical procedures planned for the relevant region, the region’s microanatomy, the anatomic features of the relevant region, and the reference values of the structures could be affected by the choice of the surgical intervention technique (eg, pterional, supraorbital, extracranial-transethmoidal, or transnasal approach) 3,4,22,24,25 . In a study performed with Indian adults aged 34.07 years by Gupta et al, 26 ONST was found as 4.83 mm (0.82), and 4.72 mm (0.74) on the left and right sides, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…It also offers tools for image registration, colocalization analysis, and 3D rendering. In research, Image J is commonly used to analyze images obtained from various techniques such as anatomy (28), histology (29), and radiology (30)(31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%